Sperm quality and in vitro fertilizing ability of boar spermatozoa stored at 4 °C versus conventional storage for 1 week - Hallberg, Ida; Morrell, Jane M.; Malaluang, Pack; Johannisson, Anders; Sjunnesson, Ylva; Laskowski, Denise (Frontiers in Veterinary Science, 2024)
IntroductionSince boar spermatozoa show a marked deterioration in sperm quality when cooled, insemination doses are usually stored at 16–18 °C. However, maintaining this temperature during transport of semen doses is challenging, particularly during the summer months. An alternative could be to store the doses at 4 °C if cold-shock to the sperm could be prevented. The objective of this study was to evaluate boar sperm quality and fertility in in vitro fertilization after storage in AndroStar Premium at 4 °C for 1 week.MethodsInsemination doses (n = 9) in AndroStar Premium from a commercial boar semen collection station were transported to the laboratory at approximately 20 °C. At the laboratory, sperm quality evaluation and was preformed and each dose was split; half of each ejaculate was stored in a climate-controlled box at 16–18 °C, the other was slowly cooled to 4 °C. Both samples were stored for 1 week before further sperm quality evaluation and in vitro fertilization (IVF) were performed. Mean values were tested using generalized linear regression, with treatment and boar as fixed factors; p ≤ 0.05 was considered significant.ResultsSperm membrane integrity (mean ± sem: 91 ± 0.05 and 83 ± 0.09% for 16 and 4 °C, respectively) and superoxide production (6.79 ± 2.37 and 13.54 ± 6.23% for 16 and 4 °C, respectively), were different between treatments. The DNA fragmentation index was lower in cold-stored samples than in conventionally stored samples (3.74 ± 2.25 and 7.40 ± 3.36% for 4 and 16 °C, respectively). The numbers of oocytes developing to blastocyst on Day 6 (mean ± sd: 9.0 ± 8.0 and 6.0 ± 5.0%, for storage at 16 and 4 °C, respectively) were not different between treatments.DiscussionTherefore, storage of boar semen doses in AndroStar Premium at 4 °C for up to 7 days would be a viable alternative to current praxis.